Bank risks and lending outcomes: Evidence from QE. (November 2021) - Sclip, Alex; Girardone, Claudia; Beltrame, Federico; Paltrinieri, Andrea
Highlights: We examine the impact of bank risk positions on lending outcomes during the Quantitative Easing interventions. We use a difference-in-difference approach and unveil that after QE1 and QE2, banks with lower default probabilities expanded lending more relative to their riskier counterparts. We find that differences in lending expansion were not present during QE3, which was announced when the banking sector health had improved to near the pre-crisis levels. Our findings suggest that bank risk positions are important for the transmission of unconventional monetary policy interventions. Abstract: This paper investigates the impact of bank risk positions on their lending outcomes during quantitative easing (QE) interventions. We find that after the first and second round of QE, banks with lower default probabilities expand lending more in comparison to their risky counterparts. However, differences were no longer relevant in the third round of QE, which occurred at a time when the banking sector health was improved relative to QE1. Our findings suggest that bank riskiness is important for the transmission of unconventional monetary policy interventions.